The Role of LncRNA TUG1 in Obesity-related Diseases - Xue, Mengzhen; Xia, Fangqi; Wang, Yaqi; Zhu, Leiqi; Li, Yuanyang; Jia, Dengke; Gao, Yan; Shi, Yue; Zhang, Changcheng; He, Yumin; Liu, Chaoqi; Yuan, Ding; et al. (Mini Reviews in Medicinal Chemistry, 2022)
As the living standards of people are increasingly improved, obesity has become a hotspot in our daily life. Obesity has been found as a chronic and recurrent disease with serious adverse consequences. Over the past few years, several articles indicated that long non-coding RNA taurine increased gene 1 (lncRNA TUG1), a useful RNA, which was indicated to show a relationship to obesity- related disease occurrence and development. Exosomes are recognized as an emerging research field that includes substances actively involved in regulating the molecular mechanisms of disease. This review summarizes the current relevant TUG1 in different molecular pathways of obesityassociated diseases, the correlation between exosomes and TUG1, or obesity-associated diseases. The aim is to explore TUG1 as a novel target for obesity, which can deepen the knowledge regarding the epigenetic regulation pathway. Furthermore, it is expected to focus on diseases associated with obesity treatment and diagnosis.
Keywords: TUG1